Pertanggungjawaban Tindak Pidana Kekerasan Seksual Ditinjau dari Hukum Pidana Positif dan Hukum Pidana Islam - Piki Rohmatuloh; Mochamad Rif’at Denasetya; Muhammad Haikal Wahyudi; Mohammad Tegar (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The aim of this research is to analyze accountability for criminal acts of sexual violence in positive criminal law and Islamic criminal law as well as violence that occurs in Indonesia. This research method uses descriptive qualitative research methods through comparative studies with a normative juridical approach which analyzes based on main legal materials by examining theories and statutory regulations, and the sources of this research are obtained from data obtained from books and scientific articles. Next, the data collected is arranged to be concluded objectively. This research concludes or provides an illustration that responsibility for criminal acts of sexual violence in positive criminal law in Indonesia is contained in article 44 of the Criminal Code, and in Islamic criminal law the responsibility is contained in Q.S. An-Nur verse 33. In this case, accountability for criminal acts of sexual violence, what must we do to protect and follow up on the perpetrators and victims of sexual violence that occurs in Indonesia, the sexual violence that occurs in Indonesia currently cannot be denied and needs to be supervision of the government and all Indonesian society.